Fast Opinion Mining using Information Retrieval techniques - Ortiz Bascuas, Jose Antonio (INFOCOMP Journal of Computer Science, 2020)
This paper focuses on the construction of models, through automatic learning, for sentimental analysis, which allow to obtain the polarity of a tweet by taking advantage of the information obtained through an information retrieval process. For this purpose, the features derived from the classification generated by such a system in response to the consultation of the document to be analyzed will be used. Through this combination of tools we will achieve a language-independent sentiment analysis, reaching accuracies comparable to other state-of-the art approaches but at a much higher speed.